CLINICAL AUDIT ON REFLEXFREE T3 TESTING AT HOSPITAL PUTRAJAYA, MALAYSIA - Kannesan, Dineash Kumar; Nasruddin, Azraai Bahari; Hussein, Zanariah; Mustapa, Siti Sarah; Anas, Siti Sharina (Journal of the ASEAN Federation of Endocrine Societies, 2024)
INTRODUCTION Reflex-free T3 (fT3) testing has long been used to optimize the use of laboratory tests in Hospital Putrajaya. It involves the automatic addition of fT3 reflexively when the TSH level is below the normal range and free T4 (fT4) is within normal limits. Excessive reflex testing can lead to an added economic burden. The objective of this audit was to determine the usefulness of reflex fT3 testing using different TSH cut-offs. METHODOLOGY Previously, fT3 was performed automatically when TSH was below the normal limits (<0.38 m IU/L) with normal fT4 (7.9 to 14.4 pmol/L). A new workflow was implemented in March where reflex fT3 was only done when TSH is <0.1 m IU/L with normal fT4. This reflex testing is only applied to adults above 18 years old. Patients who underwent reflex fT3 testing three weeks before (Group 1) and after (Group 2) implementation of the new workflow were identified. Patients who would have had reflex fT3 testing with the old workflow but not in the new workflow (TSH 0.1 - 0.37 m IU/L with normal fT4) were also identified (Group 3). Data on patient characteristics were retrospectively collected and analysed. RESULT There were 105 patients in Group 1, 66 in Group 2 and 41 in Group 3. The new TSH cut-off of <0.1 resulted in a 38% reduction in reflex fT3 testing. Only 9 (4.25%) out of the 212 patients in the 3 groups had clinical necessity for fT3 testing. The fT3 result changed management in only 6 cases. The other 3 cases were planned for follow-up with repeat tests as clinically euthyroid. CONCLUSION Reflex fT3 testing was unnecessary in a large number of cases. The usefulness of reflex fT3 testing in this cohort was very low. Hence, reflex fT3 testing is being discontinued at our centre. Further evaluation is needed to determine strategies that can optimise the ordering of fT3 tests.